Transformasi Nilai dalam Pendidikan Multikultural untuk Pengembangan Sumber Daya Manusia di Era Global - S. Wisni Septiarti; Mulyadi Mulyadi (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2007)
Education plays an important role in transferring nation values to the next generation. Moral values of a nation are likely to be influenced by global changes. Multi-cultural education seems to offer alternatives in transferring nation values successfully in this global era.